Let’s doff: a gown conservation strategy for multidrug-resistant organism colonization during the COVID-19 pandemic and beyond - Kelsey L Rowe; Josephine Fox; Carole Leone; Lydia J Grimes; Kenneth Whalen; David K Warren; Jonas Marschall (Antimicrobial Stewardship & Healthcare Epidemiology)
A COVID-19 pandemic gown conservation strategy for methicillin-resistant Staphylococcus aureus (MRSA) and vancomycin-resistant enterococci (VRE) asymptomatically colonized patients caused no significant difference in healthcare-associated MRSA (HA-MRSA) bacteremia, healthcare-associated VRE (HA-VRE) bacteremia, or healthcare-associated Clostridioides difficile infections (HA-CDI) versus prepandemic contact precautions (CP). Postpandemic HA-VRE and HA-CDI rates mirrored national trends.